2020
DOI: 10.3389/fphar.2019.01560
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Levels in Tear Film Modulate the Bioavailability of Medically-Relevant Topical Drugs

Abstract: The breakdown of blood-tear barrier that occurs with ocular pathology allows for large amounts of albumin to leak into the tear fluid. This process likely represents an important restriction to drug absorption in ophthalmology, as only the unbound drug is transported across the ocular tissue barriers to exert its pharmacologic effect. We aimed to investigate the effects of albumin levels in tears on the bioavailability of two commonly used ophthalmic drugs: tropicamide, an antimuscarinic that produces mydriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…249 although this method should account for differences between subjects such as greater tear volumes in dogs of larger body weight. 123 Another aspect to consider in the study design is the assessment of drug kinetics in diseased eyes, rendering the study results more clinically applicable (see Section 4.2); in fact, tear film concentrations and ocular bioavailability are likely to differ in healthy versus diseased eyes (e.g., excessive lacrimation, increased absorption into congested conjunctival vessels, albumin binding), 215,278 yet the majority of ocular studies to date are conducted in healthy individuals which is a clear limitation for translation of research findings from bench to bedside.…”
Section: Schirmer Strips For Drug Quantificationmentioning
confidence: 99%
See 3 more Smart Citations
“…249 although this method should account for differences between subjects such as greater tear volumes in dogs of larger body weight. 123 Another aspect to consider in the study design is the assessment of drug kinetics in diseased eyes, rendering the study results more clinically applicable (see Section 4.2); in fact, tear film concentrations and ocular bioavailability are likely to differ in healthy versus diseased eyes (e.g., excessive lacrimation, increased absorption into congested conjunctival vessels, albumin binding), 215,278 yet the majority of ocular studies to date are conducted in healthy individuals which is a clear limitation for translation of research findings from bench to bedside.…”
Section: Schirmer Strips For Drug Quantificationmentioning
confidence: 99%
“…164 Of note, the impact of lacrimal albumin on the pharmacological activity of a given drug is likely modulated by various factors including the concentration of the formulation, the mechanism of action and the potency of the drug for its biological target. 278 • Reduced bioavailability for ocular surface targets: Drug-albumin interactions in the tear film could also be detrimental for management of ocular surface disorders, for instance reducing the efficacy of therapeutics for bacterial keratitis as only the unbound portion of an antibiotic is microbiologically active. 172 Preliminary experiments conducted by the authors showed that the presence of albumin results in higher minimal inhibitory concentrations (i.e., reduced susceptibility) for various antibiotics against common bacterial isolates in dogs.…”
Section: Clinical Relevance Of Serum Albumin Leakage In Tear Filmmentioning
confidence: 99%
See 2 more Smart Citations
“…While serum albumin in tears might participate in corneal wound healing or provide antioxidative and anti-inflammatory activities, 29,30 excess levels of albumin could result in detrimental effects to the eye. Indeed, high albumin concentrations in tears were shown to decrease the bioavailability of topically administered drugs, 17,31,32 as only the unbound fraction of a drug can penetrate through the corneal barrier. Further, albumin could theoretically reduce the efficacy of topical antibiotics applied to the eye, as shown for skin wounds, 33 as only the unbound fraction of an antibiotic is microbiologically active.…”
Section: Discussionmentioning
confidence: 99%